La naissance du Parti ouvrier français : correspondence inédite de Paul Lafarge, Jules Guesde, José Mesa, Paul Brousse, Benoît Malon, Gabriel Deville, Victor Jaclard, Léon Camescasse et Friedrich Engels - Lafargue, Paul; Guesde, Jules; Mesa, José; Brousse, Paul; Malon, Benoît; Deville, Gabriël; Jaclard, Victor; Camescasse, Léon; Engels, Friedrich; Bottigelli, Emile; Willard, Claude (Paris : Éditions Sociales-Messidor, 1981)
Bibliotheek François Vercammen
Frans
Monografie